2016
DOI: 10.1039/c6ta07972e
|View full text |Cite
|
Sign up to set email alerts
|

Multipass inkjet printed planar methylammonium lead iodide perovskite solar cells

Abstract: Multipass inkjet printing and vacuum drying of MAPbI3 perovskite for better film thickness and crystal size control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
139
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 123 publications
(139 citation statements)
references
References 33 publications
0
139
0
Order By: Relevance
“…This pulse is generated by either local heating of the ink or mechanical force on the ink reservoir by a piezoelectric transducer. [88] Similar results were achieved by Mathies et al, who established a vacuum solvent extraction step to initiate a prompt crystallization, resulting in a PCE of 11.3% with an open-circuit voltage (V OC ) of 1.0 V. [32] Bag et al demonstrated that inkjet printing could also play a valuable role in research, by facilitating combinatorial screening of new materials. [81] A great variety of inks can be used, but ink formulations must be found that have the correct dynamic viscosity, density and surface tension to function correctly in the print head.…”
Section: Inkjet Printingmentioning
confidence: 62%
See 2 more Smart Citations
“…This pulse is generated by either local heating of the ink or mechanical force on the ink reservoir by a piezoelectric transducer. [88] Similar results were achieved by Mathies et al, who established a vacuum solvent extraction step to initiate a prompt crystallization, resulting in a PCE of 11.3% with an open-circuit voltage (V OC ) of 1.0 V. [32] Bag et al demonstrated that inkjet printing could also play a valuable role in research, by facilitating combinatorial screening of new materials. [81] A great variety of inks can be used, but ink formulations must be found that have the correct dynamic viscosity, density and surface tension to function correctly in the print head.…”
Section: Inkjet Printingmentioning
confidence: 62%
“…[32,91] However, traditional technologies like screen printing, gravure printing, and relief printing (flexography) are often the first choice in industry when printing of defined areas or patterns is needed. [32,91] However, traditional technologies like screen printing, gravure printing, and relief printing (flexography) are often the first choice in industry when printing of defined areas or patterns is needed.…”
Section: Screen Printing Relief Printing and Gravure Printingmentioning
confidence: 99%
See 1 more Smart Citation
“…The PCEs achieved here belong to the highest values reported for vacuum-processed NiO x HTLs without additional doping (besides the intrinsic defect doping), thus highlighting the high quality of the electron beam evaporated NiO x layer. [67][68][69][70][71] Indeed, contact angle measurements confirm a good wettability (contact angle < 90°) for the triple-cation perovskite solution on the smooth NiO x surface without spreading of the droplet (see Figure S12 in the Supporting Information). In particular, for the inkjet-printed devices, the advance from the latest reported records with stabilized PCEs of up to 18.3% for singlecation and 12.9% for triple-cation is remarkable and indicates the great promise of this technology.…”
Section: Nickel Oxide Hole Transport Layers For Efficient Perovskite-mentioning
confidence: 86%
“…Prior to the deposition of the HTL, an additional cleaning step in oxygen plasma for 3 min was performed. [67,69] Solar Cell Fabrication: In order to get working solar cells, a 25 nm thick C 60 fullerene layer (Alfa Aesar, 98%, CAS: 99685-96-8) followed by a 3 nm thick bathocuproine (Luminescence Technology, CAS: 4733-39-5) was thermally evaporated as the electron transport layers on top of the absorbers. As raw material, green NiO pieces (99.995%, Alfa Aesar, CAS: 1313-99-1) with a diameter of around 10 mm were used.…”
Section: Methodsmentioning
confidence: 99%